To Combat Extremism, How to Frame Religion Matters: Southeast Asia in Comparative Perspective - Kohno, Takeshi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
Indonesia, Malaysia, the Philippines, and Singapore are post-colonial states with diverse populations. By looking at how each state has combated Islamic extremism, this paper analyzes the state-Islam relations to identify their commonalities and differences. This paper argues that the Malaysian and Singaporean states frame Islam as a racial issue, thereby making Islam as public a matter is possible in order to achieve racial harmony. On the other hand, Indonesian and the Philippines states frame Islam as a private matter. Indonesian state lets mass Islamic organizations to manage Islam for the faithful. While in the Philippines, making the state’s influence over Islam is less effective, and it is further amplified by the state’s inability to tame Muslim’s grievances. These different policy patterns are critical in understanding the state-Islam relations during national crises, especially to explain how those countries managed the crises around the September 11, 2001 terrorist attack.